Uji Aktivitas Antibakteri Ekstrak Etanol Bulung Sangu (Gracilaria Sp.) Terhadap Bakteri Gram Negatif Pseudomonas aeruginosa - Putri, Leoni; Vernandes Sasadara, Maria Malida; Cahyaningsih, Erna; Santoso, Puguh (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2023)
Pseudomonas aeruginosa is a gram-negative bacterium that is pathogenic to humans, especially in causing nosocomial infections. This bacterium has resistance to several classes of antibiotics, one of which is carbapenem and cephalosporin class antibiotics. The development of new antibiotics is an alternative in solving this case. Seaweed is one of the marine biota that has various benefits to be developed due to its primary and secondary metabolite compounds. Secondary metabolites in seaweed are used as a source of bioactive metabolites which have broad antiviral, antifungal and antibacterial activities. Bulung sangu (Gracilaria sp.) is one of the seaweeds that has biological activity as an antibacterial. This study aims to determine the antibacterial effectiveness of 70% ethanol extract of bulung sangu (Gracilaria sp.) on the growth of Pseudomonas aeruginosa bacteria. Sangu bamboo shoots were obtained from the southern Denpasar area (Bali). Bulung sangu viscous extract was extracted using 70% ethanol by ultrasonic method for 5 minutes at 40oC. Phytochemical screening of the extract was carried out to determine the content of secondary metabolite compounds it had. Antibacterial activity testing was carried out using the well diffusion method using 3 extract concentrations namely 4%, 8% and 12%. The positive and negative controls used were chloramphenicol antibiotics and sterile aquadest. Inhibition zones were observed and expressed as mean ± standard deviation (mm). The results were statistically analyzed using Kruskal-Wallis with a 95% confidence level. The inhibition zones generated from the positive control, concentrations of 4%, 8% and 12% could inhibit Pseudomonas aeruginosa bacteria with the following average diameters of the inhibition zones of 25.67mm, 2.00mm, 2.67mm and 2.67mm in the weak inhibition zone category.